Measuring Organizational Commitment of Boomers, Gen X, Gen Y, and Gen Z: Basis for Engagement and Retention Policies - Ayo, Eliza B.; Sumande, Caroline T.; Tamayo, Josan D.; Isip, Maria Luisa G.; Wibowo M. S. , Aryo De (Future Science / FSH-PH Publications, 2025)
This study examined the organizational commitment levels of employees across four generational cohorts: Boomers, Gen X, Gen Y, and Gen Z utilizing the Three-Component Model (TCM) of Commitment. The research investigated affective, continuance, and normative commitment to identify generational differences and their influencing factors among healthcare professionals using a mixed-methods approach. The study provided insights for tailored human resource strategies to enhance employee engagement, retention, and organizational performance, setting the stage for future empirical analysis. This study explored generational differences in organizational commitment among hospital employees using a mixed-methods, cross-sectional design. Quantitative data were collected through a structured survey, assessing affective, continuance, and normative commitment. Due to small sample sizes and non-normal data distribution, the Kruskal-Wallis H test was used to compare generational groups. Qualitative data from open-ended responses were thematically analyzed to identify key factors influencing commitment, such as value alignment and workplace support. Employees show high affective commitment, driven by emotional connection, shared values, and meaningful work. Continuance and normative commitment were moderate, influenced by job stability, benefits, and a sense of loyalty. There are no significant generational differences in commitment levels, most likely due to a shared mission in healthcare. Intrinsic, value-based factors play a stronger role in commitment than external pressures.